The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1590/s0103-90162002000300015
|View full text |Cite
|
Sign up to set email alerts
|

Correlações fenotípicas entre caracteres vegetativos e de produção de palmito da palmeira real australiana

Abstract: A seleção indireta é prática corrente no melhoramento de plantas perenes e vem sendo usada com sucesso em programas de melhoramento genético de palmeiras visando a produção de palmito. O objetivo do trabalho foi auxiliar na identificação dos caracteres de natureza não destrutiva que possam ser utilizados futuramente na indicação de palmeiras aptas à colheita e na seleção indireta de plantas superiores de palmeira real australiana (Archontophoenix alexandrae Wendl. & Drude). Em uma população de palmeiras co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Wide morphological variability in fruit morphology is typical of wild, non-selected species, and is indicative of high genetic diversity, which was confirmed by work with molecular markers performed in the same region of this study (SANTOS et al, 2014). The high variability that exists in natural populations allows for rapid and significant gains in genetic improvement programs during the first phases of selection (UZZO et al, 2002;BORÉM;MIRANDA, 2005;GROSS;OLSEN, 2010) and could favor the economic development of A. vitrivir.…”
Section: Discussionmentioning
confidence: 99%
“…Wide morphological variability in fruit morphology is typical of wild, non-selected species, and is indicative of high genetic diversity, which was confirmed by work with molecular markers performed in the same region of this study (SANTOS et al, 2014). The high variability that exists in natural populations allows for rapid and significant gains in genetic improvement programs during the first phases of selection (UZZO et al, 2002;BORÉM;MIRANDA, 2005;GROSS;OLSEN, 2010) and could favor the economic development of A. vitrivir.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in E. oleracea, Oliveira et al (2000) found that the stipe diameter and the number of live leaves were correlated with production traits, enabling early selection for the species. In Archontophoenix alexandrae, significant positive correlations were found between vegetative traits, such as stipe diameter, plant height, number of leaves, and the fourth sheet length, with direct components of palm heart production (Uzzo et al 2002). In addition, it was found that these correlations are valid since the beginning of cultivation, indicating the possibility of early selection of superior plants for the fruit production on the stipe diameter, the height, and the number of tillers (Bovi et al 1990).…”
Section: Genetic Parameters Based On Joint Analysismentioning
confidence: 92%